2014
DOI: 10.4236/ajps.2014.526414
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Three Antiporter Genes from Arabidopsis and Rice for Over-Expressing Them in Farmer Popular Tomato Varieties of Bangladesh

Abstract: Salinity is one of the most critical environmental problems, which causes plant growth retardation by disturbing intracellular ion homeostasis. The Na + /H + antiporter plays an important role in resistance to salt stress by sequestering Na + in exchange for H + across the vacuolar membranes. In the current study, the coding regions of two Arabidopsis antiporters (AtNHX1 and AtNHX2) and one rice antiporter (OsNHX1) were amplified by target specific PCR. PCR amplicons were first cloned into pENTR/D-TOPO and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…antiporter increased upon treatment with NaCl and showed more increase plant tolerance to NaCl in transformants plants compared to wild types (Yu et al 2007;DoraniUliaie et al 2012). Also, overexpression of AtNHX1 in tomato resulted in transgenic plants that were able to grow, flower and set fruits at higher salt concentrations (Zhang and Blumwald 2001;Razzaque et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…antiporter increased upon treatment with NaCl and showed more increase plant tolerance to NaCl in transformants plants compared to wild types (Yu et al 2007;DoraniUliaie et al 2012). Also, overexpression of AtNHX1 in tomato resulted in transgenic plants that were able to grow, flower and set fruits at higher salt concentrations (Zhang and Blumwald 2001;Razzaque et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Then, for RE analysis [28,29], a 2-3 white/light blue colonies were inoculated into 5mL selective LB broth and shaken at 150 rpm, 37 o C overnight. The recombinant vector was isolated from the overnight cultured using Invitrogen Pure Link TM Quick Plasmid Miniprep kit as described by the manufacturer.…”
Section: Screening Of Positive Transformantsmentioning
confidence: 99%
“…Consequently, transformed cells containing the recombinant vector without the functional β-galactosidase may be formed as white or light blue on the plate. The compound is cleaved by β-galactosidase to form 5-bromo-4-chloro-indoxyl, that spontaneously oxidizes and dimerizes to form a bright blue insoluble pigment 5,5'-dibromo-4,4'-dichloro-indigo [29,60,61]. The blue colonies characteristic, hence, showed that the cells contain an uninterrupted lacZ gene or fully functional β-galactosidase enzyme, whereas the white/light blue colonies (X-gal is not hydrolyzed) indicated the presence recombinant vector in the bacterial cells [62].…”
Section: Construction Of Rft1 Gene and Transformation Analysismentioning
confidence: 99%